Law, cultural studies and the 'Burqa Ban' trend : an interdisciplinary handbook - Matwijkiw, Anja; Oriolo, Anna (Cambridge : Intersentia, 2021)
This book offers an in-depth account of the 'burqa ban' trend, bringing together law and cultural studies. With a focus on Europe and America, leading academics and professionals provide insights to value and identity politics, diversity, discrimination, human rights and the discussions surrounding the national and international courts' contradictory judgments.
Title from publisher's bibliographic system (viewed on 10 Dec 2021).
Keywords: Burqas (Islamic clothing) -- Law and legislation -- Europe -- Congresses; Burqas (Islamic clothing) -- Law and legislation -- United States -- Congresses; Freedom of religion; Human rights